Amplification of DNA from whole blood. - Burckhardt, J

(untitled) (Genome Research, 1994)
A method is described for the amplification by PCR of human chromosomal DNA sequences from whole blood samples. Various amounts of blood samples, with either EDTA, citrate, or heparin used as the anticoagulant, have been used to determine optimal PCR conditions for each type of sample. Up to 80% (vol/vol) of whole blood sample is tolerated in PCR with Taq polymerase. Amplification from whole blood requires the optimization of salt (K+ and Mg++) according to sample volume and type of anticoagulant used. Pretreatment of fresh blood samples to lyse the leukocytes is required for EDTA-treated blood samples and is beneficent in PCR with heparin- and citrate-treated blood samples to obtain maximal amplicon amounts. A satisfactory method of pretreating samples is freeze/thawing. In addition, EDTA-treated blood samples require a heat treatment before PCR for maximal amplicon synthesis. It appears that purification of the DNA is not necessary for any of the whole blood samples analyzed by PCR. Results of amplification reactions from unpurified hepatitis B virus (HBV) sequences of whole sera samples are shown also.